Pengaruh Net Profit Margin, Return on Asset & Leverage terhadap Income Smoothing serta Dampaknya terhadap Kinerja Keuangan pada Bank Umum Syariah di Indonesia - Maula Nasrifah (Iqtishodiyah : Jurnal Ekonomi dan Bisnis Islam, 2017)
Income Smoothing is a disclosure method of a company financial reporting which aims to smoothen the profit from one period to another period. This is made by the management with the objective to indicate a good financial performance so that it can attract the investors to place their funds in the company looking into a steady profit offered. The study aims to analyze the impact of Net Profit Margin, Return On Asset and Leverage variables to the Income Smoothing as well as Financial Performance of full-fledged Islamic banks in Indonesia using financial reporting data year 2010-2103. The study employs a regression analysis developed into Path Analysis and Triming Model. The date is tested by the classic assumption tests, namely normality, heteroscedasticity, multicollinearity and auto correlation. The hypothesis test is computed by Software SPSS Versi 21.0. The analysis result shows that Net Margin Profit is the only variable with a statistically significant impact toward Income Smoothing. Return on Asset and Leverage do not significantly impact the Income Smoothing. In addition to that, Net Profit Margin influences the Financial Performance of the bank. Furthermore, Return on asset, leverage, and Income Smoothing do not show a statistically significant impact to the Financial Performance.